Cyanate ester resins containing pentadecyl-substituted cyclohexyl moiety: synthesis, curing and structure-property relationship - Kulkarni, Arun D.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (High Performance Polymers, 2013)
Cyanate ester (CE) monomers containing pentadecyl-substituted cyclohexyl moieties such as 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane and 1,1-bis(4-cyanatophenyl) cyclohexane were synthesized and characterized by Fourier transform infrared, proton-nuclear magnetic resonance (H-1-NMR) and carbon-nuclear magnetic resonance (C-13-NMR) spectroscopies as well as differential scanning calorimetry (DSC). Both 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane and 1,1-bis(4-cyanatophenyl) cyclohexane exhibited better processability coupled with lower melting points, lower cure onset with broad cure exotherm than the commercially available CE monomer, namely, 2,2-bis(4-cyanatophenyl) propane. Glass transition temperatures of cured 2,2-bis(4-cyanatophenyl) propane, 1,1-bis(4-cyanatophenyl) cyclohexane and 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane were observed to be 288 degrees C, 302 degrees C and 160 degrees C, respectively. Cured 1,1-bis(4-cyanatophenyl) cyclohexane displayed higher storage modulus (1.59 x 10(9) Pa) than 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane (1.07 x 10(9) Pa) and 2,2-bis(4-cyanatophenyl) propane (1.39 x 10(9) Pa). The order of thermal stability of cured polycyanurates was found to be 2,2-bis(4-cyanatophenyl) propane > 1,1-bis(4-cyanatophenyl) cyclohexane > 1,1-bis(4-cyanato phenyl) 3-pentadecylcyclohexane. The moisture absorption of cured resins derived from 1,1-bis(4-cyanatophenyl) 3-pentadecyl cyclohexane and 1,1-bis(4-cynatophenyl) cyclohexane was found to be lower than that of 2,2-bis(4-cynatophenyl) propane implying the role of pentadecyl substituent and/or cyclohexyl moiety in imparting hydrophobicity to the polycyanurates.
Keywords: (pentadecyl substituted) cyclohexyl; curing; cyanate ester resin; thermosets

Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs): a new heterogeneous and recyclable catalyst for the one pot synthesis of 1,4-disubstituted-1,2,3-triazoles in water - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (RSC Advances, 2014)
Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs) have been demonstrated for the first time as an efficient heterogeneous catalyst in the click synthesis of 1,4-disubstituted 1,2,3-triazoles by a one-pot three component reaction between aralkyl/alkyl bromides, alkynes and sodium azide in water. The catalyst has been characterized by XRD, HRTEM, SEM, ICP-AES, EDS as well as IR spectroscopy. It was found to be reusable for five consecutive runs without significant loss of activity.

Cobalt ferrite nanoparticles: a magnetically separable and reusable catalyst for Petasis-Borono-Mannich reaction - Kulkarni, Aparna M.; Pandit, Kapil S.; Chavan, Pramod V.; Desai, Uday V.; Wadgaonkar, Prakash P. (RSC Advances, 2015)
Magnetically separable cobalt ferrite nanoparticles (CoFe2O4, NPS) have been demonstrated for the first time as an efficient catalyst in Petasis-Borono-Mannich (PBM) reaction between salicylaldehydes, sec. amines and aryl boronic acids to furnish alkylaminophenols in high yields. Relatively shorter reaction times, easy purification of the products and reusability of the catalyst for five consecutive runs without appreciable loss in it's activity are the noteworthy features of the developed protocol.

Convenient synthesis of alpha,alpha `- homo- and alpha,alpha `-hetero-bifunctionalized poly(epsilon-caprolactone)s by ring opening polymerization: the potentially valuable precursors for miktoarm star copolymers - Patil, Sachin S.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
Two new ring opening polymerization (ROP) initiators, namely, (3-allyl-2-(allyloxy)phenyl)methanol and (3-allyl-2-(prop-2-yn-1-yloxy)phenyl)methanol each containing two reactive functionalities viz. allyl, allyloxy and allyl, propargyloxy, respectively, were synthesized from 3-allylsalicyaldehyde as a starting material. Well defined -allyl, -allyloxy and -allyl, -propargyloxy bifunctionalized poly(epsilon-caprolactone)s with molecular weights in the range 4200-9500 and 3600-10,900 g/mol and molecular weight distributions in the range 1.16-1.18 and 1.15-1.16, respectively, were synthesized by ROP of epsilon-caprolactone employing these initiators. The presence of -allyl, -allyloxy and -allyl, -propargyloxy functionalities on poly(epsilon-caprolactone)s was confirmed by FT-IR, H-1, C-13 NMR spectroscopy, and MALDI-TOF analysis. The kinetic study of ROP of epsilon-caprolactone with both the initiators revealed the pseudo first order kinetics with respect to epsilon-caprolactone consumption and controlled behavior of polymerization reactions. The usefulness of -allyl, -allyloxy functionalities on poly(epsilon-caprolactone) was demonstrated by performing the thiol-ene reaction with poly(ethylene glycol) thiol to obtain (mPEG)(2)-PCL miktoarm star copolymer. -Allyl, -propargyloxy functionalities on poly(epsilon-caprolactone) were utilized in orthogonal reactions i.e copper catalyzed alkyne-azide click (CuAAC) with azido functionalized poly(N-isopropylacrylamide) followed by thiol-ene reaction with poly(ethylene glycol) thiol to synthesize PCL-PNIPAAm-mPEG miktoarm star terpolymer. The preliminary characterization of A(2)B and ABC miktoarm star copolymers was carried out by H-1 NMR spectroscopy and gel permeation chromatography (GPC). (c) 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2016, 54, 844-860
Keywords: 3-allylsalicyaldehyde; alpha `-allyloxy and alpha-allyl; alpha `-propargyloxy bifunctionalized poly (epsilon-caprolactone)s; alpha-allyl; atom transfer radical polymerization; orthogonal reactions; ring-opening polymerization; star copolymers

Click-chemistry-based multicomponent condensation approach for design and synthesis of spirochromene-tethered 1,2,3-triazoles as potential antitubercular agents - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Wadgaonkar, Prakash P.; Nawale, Laxman; Bhansali, Sujit; Sarkar, Dhiman (Research on Chemical Intermediates, 2017)

Click chemistry based multicomponent approach in the synthesis of spirochromenocarbazole tethered 1,2,3-triazoles as potential anticancer agents - Chavan, V, Pramod; Desai, V, Uday; Wadgaonkar, Prakash P.; Tapase, Savita R.; Kodam, Kisan M.; Choudhari, Amit; Sarkar, Dhiman (Bioorganic Chemistry, 2019)
A series of spirochromenocarbazole tethered 1,2,3-triazoles were synthesized via click chemistry based one-pot, five component reaction between N-propargyl isatins, malononitrile, 4-hydroxycarbazole, aralkyl halides and sodium azide using cellulose supported CuI nanoparticles (Cell-CuI NPs) as the heterogeneous catalyst. Antiproliferative activity of all the synthesized compounds was investigated against panel of cancer cell lines such as MCF-7, MDA-MB-231, HeLa, PANG-1, A-549, and THP-1. Many of the synthesized compounds exhibited good anti-proliferative activity against breast (MCF-7 and MDA-MB-231) and cervical (HeLa) cancer cells with IC50 values less than 10 mu M. In case of MCF-7 cells, among the nine compounds that showed good anti-proliferative activity, compounds 6f and 6j were found to be highly potent (IC50 , = 2.13 mu M and 4.80 mu M, respectively). In case of MDA-MB-231, three compounds (6k, 6j and 6s) showed antiproliferative activity amongst which 6k was the most potent one (IC50 = 3.78 mu M). On the other hand, in cervical cancer HeLa cells, compounds 6b, 6g, 6s and 6u showed excellent antiproliferative activity (IC50 = 4.05, 3.54, 3.83, 3.35 mu M, respectively). All the compounds were found to be nontoxic to the human umbilical vein endothelial cells (HUVECs). AO and EtBr staining and fluorescence microscopy studies of the active compounds (IC50 < 5 mu M) suggested that these compounds induce cell death by apoptosis.
Keywords: 1; 2; 3-Triazolylspirochromenocarbazole; Anticancer; Apoptotic assay; Click chemistry; Cytotoxicity; heterogeneous catalysis; Multicomponent synthesis

Catechol- and phenolic hydroxyl-functionalized partially bio-based (Co) poly(ether sulfone)s with multifarious applicability - Wale, Apparav K.; Jagtap, Ashish S.; Pandey, Priyanshi R.; Dastager, Syed G.; Shelke, Manjusha V.; Ambade, Ashootosh V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2024)
A largely bio-based new bisphenol, namely, 4,4 `-((3,4-dimethoxyphenyl)methylene)-bis(2-methoxyphenol) (DMBM) was synthesized by the reaction of veratraldehyde with guaiacol. DMBM and varying compositions of DMBM and bisphenol A were polycondensed with bis(4-fluorophenyl) sulfone to afford reasonably high molecular weight film-forming (co)poly(ether sulfone)s possessing built-in methoxyl groups. T10 and Tg values of (co)poly(ether sulfone)s were in the range 382-478 degrees C and 171-187 degrees C, respectively indicating their good thermal stability and the values decreased with increase in mol % incorporation of DMBM. The methoxyl groups present in (co)poly (ether sulfone)s were quantitatively de-blocked resulting in the formation of corresponding polymers possessing pendant catechol moieties and free phenolic hydroxyl groups. By virtue of the presence of these functional moieties, (co)poly(ether sulfone)s are amenable for post-polymerization modifications, and exhibited properties such as antimicrobial (23 mm against Staphylococcus aureus and 18 mm against Escherichia coli)), antioxidant (72 % scavenger of free radicals), adhesive (2.24 MPa lap shear strength) and usefulness as redox-active agent in zinc-ion batteries. These data underscore the promise of DMBM as a versatile monomer of wider utility for the synthesis of functional (co)poly(ether sulfone)s capable of expanding their applicability beyond the conventional ones.
Keywords: (Co)poly(ether sulfone)s; adhesive; Antimicrobial; Antioxidant; bio-based; bisphenol; Zinc-ion batteries